1987
DOI: 10.1172/jci112906
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and pathogenesis of stunned myocardium. Depressed Ca2+ activation of contraction as a consequence of reperfusion-induced cellular calcium overload in ferret hearts.

Abstract: Contractile dysfunction in stunned myocardium could result from a decrease in the intracellular free [Ca2+1 transient during each beat, a decrease in maximal Ca2+-activated force, or a shift in myofilament Ca2+ sensitivity. We measured developed pressure (DP) at several [Cal6 (0.5-7.5 mM) in isovolumic Langendoriperfused ferret hearts at 370C after 15 min of global ischemia (stunned group, n = 13) or in a nomnschemic control group (a = 6). At all ICal6, DP was depressed in the stunned group (P < 0.001). Maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0
5

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(134 citation statements)
references
References 42 publications
2
127
0
5
Order By: Relevance
“…The significantly greater increase in intracellular [Ca 2ϩ ] in CK-deficient hearts at the end of the ischemic period, however, has a significant impact on the subsequent reperfusion injury, known to be mediated by the transient Ca 2ϩ overload within the first minutes of reperfusion (12). During the course of reperfusion, systolic and diastolic LV performance remained significantly impaired in both groups of hearts despite lower resting [Ca 2ϩ ] during reperfusion.…”
Section: Discussionmentioning
confidence: 93%
“…The significantly greater increase in intracellular [Ca 2ϩ ] in CK-deficient hearts at the end of the ischemic period, however, has a significant impact on the subsequent reperfusion injury, known to be mediated by the transient Ca 2ϩ overload within the first minutes of reperfusion (12). During the course of reperfusion, systolic and diastolic LV performance remained significantly impaired in both groups of hearts despite lower resting [Ca 2ϩ ] during reperfusion.…”
Section: Discussionmentioning
confidence: 93%
“…First, when isolated ferret hearts subjected to 15 minutes of global normothermic ischemia are reperfused with solutions containing low concentrations of calcium, the postischemic contractile abnormalities are significantly attenuated. 27 The results of this experiment, in which no intervention is applied during ischemia, indicate that calcium entry upon reperfusion is an important mechanism of myocardial stunning. A decrease in the severity of stunning is also observed in hearts pretreated with ryanodine, an inhibitor of cellular calcium overload.29 Second, exposure of isolated ferret hearts to a transient calcium overload in the absence of ischemia produces mechanical and metabolic abnormalities similar to myocardial stunning.…”
Section: Decreased Sensitivity Of Myofilaments To Calciummentioning
confidence: 83%
“…Myocardial stunning probably arises from the additive effects of a reperfusion-induced pathology (identified, as least in part, by the fraction [dark shading] of the contractile deficit, which can be restored through the use of an antioxidant intervention given transiently at the time of reperfusion) and a second component (light shading), which incorporates the ischemic pathology from which the heart is slowly recovering, together with any additional reperfusion-induced component that is not amenable to the chosen intervention. 14,17,28,60 ( Fig 1A). Indirect evidence indicates that Ca 2ϩ overload also contributes to postischemic dysfunction after regional ischemia in vivo, 63 but direct demonstration of this concept is still lacking.…”
Section: ؉mentioning
confidence: 95%
“…Studies in models of stunning after global ischemia in vitro 14,15 and in ventricular trabeculae isolated from these models 61 have concluded that the alteration responsible for the contractile dysfunction consists of a decrease both in the maximal Ca 2ϩ -activated force and the sensitivity of myofilaments to Ca 2ϩ . A decrease in Ca 2ϩ sensitivity of myofilaments has not been observed consistently in all models of global ischemia in vitro, however.…”
Section: ؉mentioning
confidence: 99%